Emergency Education Policy: EFL Undergraduate Students’ Views on Online Learning during the COVID-19 Pandemic - Eddy Haryanto (Indonesian Research Journal in Education |IRJE|, 2021)
Anchored by sparse investigations on Students’ voices regarding online learning from home during the COVID-19 pandemic in developing countries context, this study aims to investigate the responses of EFL students to the effectiveness of the learning from home policy in an Indonesian University. Fifteen students of fourth semester studying at English department were recruited. This research employed qualitative design with a case study approach as the methodology.  Data were collected from semi-structured interview and then analyzed descriptively. The results showed that the students perceived that online learning from home was good policy initiatives. However, they also experienced ineffectiveness regarding the contents of learning that focus more on giving students the assignments than the learning process itself. Besides that, the students were not supported by conducive learning environment, enabling them to learn more effectively. Students experienced some problems during online learning from home, such as poor internet connection, electrical power disruptions, and day-to-day load expenses for prepaid internet access. The findings suggest that the lecturers should provide the students with appropriate learning instruction for online learning purposes and deliver teaching materials by making use of technology. Thus, policy recommendations are discussed in this article.